Supercomplexes of plant photosystem I with cytochrome b6f, light-harvesting complex II and NDH - Yadav, K N Sathish; Semchonok, Dmitry A; Nosek, Lukáš; Kouřil, Roman; Fucile, Geoffrey; Boekema, Egbert J; Eichacker, Lutz A (Biochimica et biophysica acta. Bioenergetics, 2017)
Photosystem I (PSI) is a pigment-protein complex required for the light-dependent reactions of photosynthesis and participates in light-harvesting and redox-driven chloroplast metabolism. Assembly of PSI into supercomplexes with light harvesting complex (LHC) II, cytochrome b6f (Cytb6f) or NAD(P)H dehydrogenase complex (NDH) has been proposed as a means for regulating photosynthesis. However, structural details about the binding positions in plant PSI are lacking. We analyzed large data sets of electron microscopy single particle projections of supercomplexes obtained from the stroma membrane of Arabidopsis thaliana. By single particle analysis, we established the binding position of Cytb6f at the antenna side of PSI. The rectangular-shaped Cytb6f dimer binds at the side where Lhca1 is located. The complex binds with its short side rather than its long side to PSI, which may explain why these supercomplexes are difficult to purify and easily disrupted. Refined analysis of the interaction between PSI and the NDH complex indicates that in total up to 6 copies of PSI can arrange with one NDH complex. Most PSI-NDH supercomplexes appeared to have 1-3 PSI copies associated. Finally, the PSI-LHCII supercomplex was found to bind an additional LHCII trimer at two positions on the LHCI side in Arabidopsis. The organization of PSI, either in a complex with NDH or with Cytb6f, may improve regulation of electron transport by the control of binding partners and distances in small domains.
Keywords: Electron microscopy; Cytochrome b6f Complex; Photosystem I; Photosystem I Protein Complex; fotosyntéza; Arabidopsis; chloroplasty; Photosynthesis; Chlorophyll; Supercomplex; transport elektronů; Chloroplasts; NADH-dehydrogenasa; fotosystém I (proteinový komplex); Thylakoids; světlo; oxidace-redukce; Electron Transport; chlorofyl; Light-Harvesting Protein Complexes; tylakoidy; NADH Dehydrogenase; Cytochrome b(6)f complex; Oxidation-Reduction; světlosběrné proteinové komplexy; komplex cytochromů b6f; Light; NDH